Analysis Of Implementation Of Posyandu Service Policy In Lawang Agung Village - Lorita, Evi; Saputra, Harius Eko; Anggraini, Fitri (Utan Kayu Publishing, 2023)
This study aims to analyze the implementation of the Posyandu service policy in Lawang Agung Village, South Bengkulu Regency, with a focus on evaluating the success and challenges in its implementation. Using a qualitative descriptive approach, data were obtained through observation, interviews, and documentation from various informants, including health center officers, Posyandu cadres, and community service recipients. The policy evaluation was conducted based on the Wayne Parsons model, which includes formative and summative evaluations. The results of the study indicate that most Posyandu programs, such as maternal and child nutrition services, disease control, clean and healthy living behavior, and elderly health services, have been integrated and run effectively. However, several services such as Pos PAUD have not been optimally implemented due to lack of socialization and low public awareness. Summative evaluation indicates a significant increase in public health indicators, such as a decrease in maternal and infant mortality rates and increased awareness of healthy lifestyles. The success of this program is supported by the availability of human resources, additional food, facilities and infrastructure, and budget support from the village government. This study recommends increasing socialization and community participation to strengthen the effectiveness of Posyandu services in the future.